2012
DOI: 10.1111/j.1365-2702.2012.04235.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of Turkish Caregiver Burden Scale among family caregivers of haemodialysis patients

Abstract: The burden experienced by people who provide care for patients with chronic diseases can be evaluated with the Caregiver Burden Scale. Additionally, the Caregiver Burden Scale can be used in the evaluation of the effectiveness of attempts to decrease caregiver burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…This subjectivity has widely been studied in the informal caregiving literature in the form of subjective burden , the subjective weight of being a caregiver ( Chiao et al, 2015 ). Studies have consistently shown a positive relationship between subjective burden and burnout among informal caregivers (e.g., Truzzi et al, 2008 ; Cill Akinci and Pinar, 2014 ). In the professional literature, similar findings exist with related variables: the accumulation of subjective stressors is a better predictor of professional burnout than the quantity or type of objective stressors themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This subjectivity has widely been studied in the informal caregiving literature in the form of subjective burden , the subjective weight of being a caregiver ( Chiao et al, 2015 ). Studies have consistently shown a positive relationship between subjective burden and burnout among informal caregivers (e.g., Truzzi et al, 2008 ; Cill Akinci and Pinar, 2014 ). In the professional literature, similar findings exist with related variables: the accumulation of subjective stressors is a better predictor of professional burnout than the quantity or type of objective stressors themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies observed that mental health, vitality of the patient, type of relationship, pain[14] social aspect, pain, vitality, hours per week,[13] living with patient,[21] and mental and physical component[23] in caregivers of HD undergoing patients; mental component of caregiver and patients[13] in caregivers of PD undergoing patients; and male gender, marital status, low educational level, spouse or parent as caregivers and adverse effects on patient second transplant in caregivers of RT patients[32] were found to be the significant factors associated with caregiver burden.…”
Section: Discussionmentioning
confidence: 99%
“…[131435] Physical component summary score of QOL was found to be contributing 55.8%, 48.3%, and 43.3% for the burden score in caregivers of HD and PD undergoing and RT patients and indicated that it is a major component for causing burden among caregivers of patients undergoing all the three RRT. Earlier studies showed physical component in pooled dialysis caregivers;[19] mental component[14] or mixed physical and mental component in caregivers of HD; and mental component in caregivers of PD[1323] contribute largely to the burden score. It is interesting to note that coping mechanisms responsible for burden score were found to be different for caregivers of patients undergoing each modality of RRT (seeking social support and accepting responsibility in HD; self-controlling in PD; and escape avoidance in RT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments in medicine and rapid changes in individuals' living conditions have led to changes in people's health and disease patterns, resulting in a decrease in acute diseases. Conversely, chronic diseases are becoming factors threatening people's health through irreversible pathological changes and constant unusual conditions . One of the medical treatments for chronic kidney disease (CKD) is hemodialysis (HD), which is a safe and effective way to help patients by not only prolonging their lives, but also maintaining their health in a relatively good condition.…”
Section: Introductionmentioning
confidence: 99%